The Relationship of Husband's Support and the Attitudes of Pregnant Women in the 1st Trimester in Overcoming Emesis Gravidarum in the Working Area of the Kasiyan Health Center - Deviyanti, Serly; Bachri, Syaiful (D'Nursing and Health Journal (DNHJ), 2025)
Introduction: Emesis Gravidarum in pregnancy is one of the complaints that is often experienced by pregnant women in the first trimester. Emesis garvidarum can be overcome, among other things, by consuming food and drinks in the right way according to recommendations, and this is influenced by attitude. Husband's support plays an important role in shaping the attitudes of pregnant women. Research Objective: to analyze the relationship between husband's support and the attitude of pregnant women in the first trimester in dealing with emesis gravidarum in the working area of ​​the Kasiyan Community Health Center. Method: The research design is an analytic survey with a cross-sectional approach, with a population of 40 pregnant women and a sample of 36 pregnant women using proportionate random sampling technique. The data collection tool used is a questionnaire. Result: Based on the calculations, almost all pregnant women received support from their husbands 55.56%, and almost all first-trimester pregnant women had a positive attitude in dealing with emesis gravidarum 55.56%. Conclusion: The Chi-Square test results showed a p-value of 0.009 < 0.05, indicating a significant relationship between husband’s support and the attitude of first-trimester pregnant women in dealing with emesis gravidarum in the working area of Kasiyan Health Center, with a strong correlation.